Post‐tsunami reconstruction in sri lanka: Assessing the economic impact - Ruddock, Les; Amaratunga, Dilanthi; Wanigaratne, Nadeeshani; Palliyaguru, Roshani (International Journal of Strategic Property Management, 2010)
The “construction output shock” that was generated by the massive reconstruction programmes after the Indian Ocean tsunami in Sri Lanka spread through the economic system and was reflected in economic indicators due to the multiple linkages that the construction industry has with other economic sectors. On the ground, it was observed that the prices of construction materials, labour and plant rose suddenly in the affected regions making the reconstruction effort more costly. This paper considers the responses of major economic and construction indicators to the construction shock due to post‐tsunami reconstruction and the amount of time needed before they returned to an equilibrium state. Empirical results indicate that the construction output shock had a significant impact on material, labour and equipment price indices in the short run but other indicators showed only a very marginal response indicating that the remoteness of the disaster would have delayed the propagation. First Published Online: 09 Jun 2011